2019
DOI: 10.1021/jacs.8b13543
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Strategy for Tuning ORR Activity of a Single Fe-N4 Site by Controlling Electron-Withdrawing/Donating Properties of a Carbon Plane

Abstract: Replacement of Pt-based oxygen reduction reaction (ORR) catalysts with non-precious metal catalysts (NPMCs) such as Fe/N/C is one of the most important issues in the commercialization of proton exchange membrane fuel cells (PEMFCs). Despite numerous studies on Fe/N/C catalysts, a fundamental study on the development of a versatile strategy is still required for tuning the kinetic activity of a single Fe-N4 site. Herein, we report a new and intuitive design strategy for tuning and enhancing the kinetic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
442
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(473 citation statements)
references
References 57 publications
8
442
0
1
Order By: Relevance
“…Based on a similar synergistic mechanism, FeN 4 on B‐doped carbon supports was also developed for improved ORR activity . Recently, Mun et al reported that the electron‐withdrawing/donating properties of carbon substrates are indicative of Fe–N 4 ORR activity in acidic media, control of which was achieved by tuning the S doping ( Figure 5 a) . However, the opposite trend was observed for the effect of electronegativity on the activity of FeN x sites.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a similar synergistic mechanism, FeN 4 on B‐doped carbon supports was also developed for improved ORR activity . Recently, Mun et al reported that the electron‐withdrawing/donating properties of carbon substrates are indicative of Fe–N 4 ORR activity in acidic media, control of which was achieved by tuning the S doping ( Figure 5 a) . However, the opposite trend was observed for the effect of electronegativity on the activity of FeN x sites.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…However, the electronic modulation mechanisms remain controversial. The DFT calculations in many studies suggest that the reductive release of OH* (*OH + 3OH − + e − → 4OH − + *) should be the rate‐limiting step if the ORR pathway follows the associative mechanism because the adsorption of OH* intermediates on the Fe center is too strong . The expected role of S doping is therefore to weaken the OH* binding which improves ORR activity and kinetics.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 99%
“…The experiment and DFT calculation have demonstrated that the OER catalysts following the activity tendency of Ni > Co > Fe. Lee and co‐workers have reported that S‐doping can incorporate electron‐donating/withdrawing function in carbon plane, which can change the charge state of the FeN 4 and provide an optimal intermediates adsorption energy, and thus accelerate the ORR reaction …”
Section: Intramolecular Charge Transfermentioning
confidence: 99%
“…Mun et al report a versatile strategy to incorporate electron‐withdrawing/donating functionalities on the carbon plane by S‐doping ( Figure 4 ). The strength of the electronic effect, derived from the delocalized π‐band of the carbon plane on the d‐orbital of the Fe ion in the Fe–N 4 site results in a beneficial change of ORR activity of the Fe–N 4 site …”
Section: Iron‐based Electrocatalystsmentioning
confidence: 99%
“…The thiophene‐like S functionality gives an electron‐donating effect, and the oxidized S functionality gives an electron‐withdrawing effect to the Fe–N 4 site. Adapted with permission . Copyright 2019, ACS.…”
Section: Iron‐based Electrocatalystsmentioning
confidence: 99%